Serendipita indica: A Promising Biostimulant for Improving Growth, Nutrient Uptake, and Sugar Accumulation in Camellia oleifera - Wan-Lin Fu; Wei-Jia Wu; Zhi-Yan Xiao; Fang-Ling Wang; Jun-Yong Cheng; Ying-Ning Zou; Abeer Hashem; Elsayed Fathi Abd_Allah; Qiang-Sheng Wu (Horticulturae)
Serendipita indica is a very promising root-associated endophytic fungus that is widely used on various plants; however, whether it affects the growth and physiological activity of an oilseed crop (Camellia oleifera) under field conditions remains unclear. In this study, we analyzed the effects of S. indica inoculation on root colonization rate, growth rate, photosynthetic parameters, mineral element concentrations and related gene expression, and sugar concentrations and expression of their transporter genes in four-year-old C. oleifera trees in the field. The results showed that the root colonization rate of C. oleifera increased from 3.37% to 9.42% following being inoculated with S. indica. Inoculation with S. indica significantly increased the plant height (46.81%), net photosynthetic rate (69.16%), nitrogen balance index (14.44%), chlorophyll index (21.08%), leaf K (7.4%), leaf Ca (13.52%), root P (17.75%), root K (12.80%), soil NH4+-N (17.78%), available K (26.66%), Olsen-P (184.30%), easily extractable glomalin-related soil protein (39.26%), and soil organic carbon (16.25%) concentrations compared to the uninoculated treatment. Inoculation with S. indica also significantly up-regulated the expression of CoHKT1;1 and CoCAX1;2 in the leaves and roots and CoPht1;1, CoPht1;2, and CoPht1;3 in the leaves. Plants inoculated with S. indica also presented significantly higher leaf glucose, fructose, and sucrose concentrations, accompanied by up-regulated expression of CoSWEET2a, CoSWEET7, CoSWEET9b, CoSWEET17a, and CoSWEET17b. These results suggest that S. indica has significant potential as a biostimulant for enhancing the growth and nutritional profile of C. oleifera, thereby contributing to sustainable oilseed production.